Microfabrication Technologies for Nanoinvasive and High-Resolution Magnetic Neuromodulation - Ge, Changhao; Masalehdan, Tahereh; Shojaei Baghini, Mahdieh; Duran Toro, Vicente; Signorelli, Lorenzo; Thomson, Hannah; Gregurec, Danijela; Heidari, Hadi (Advanced Science, 2024)
The increasing demand for precise neuromodulation necessitates advancements in techniques to achieve higher spatial resolution. Magnetic stimulation, offering low signal attenuation and minimal tissue damage, plays a significant role in neuromodulation. Conventional transcranial magnetic stimulation (TMS), though noninvasive, lacks the spatial resolution and neuron selectivity required for spatially precise neuromodulation. To address these limitations, the next generation of magnetic neurostimulation technologies aims to achieve submillimeter-resolution and selective neuromodulation with high temporal resolution. Invasive and nanoinvasive magnetic neurostimulation are two next-generation approaches: invasive methods use implantable microcoils, while nanoinvasive methods use magnetic nanoparticles (MNPs) to achieve high spatial and temporal resolution of magnetic neuromodulation. This review will introduce the working principles, technical details, coil designs, and potential future developments of these approaches from an engineering perspective. Furthermore, the review will discuss state-of-the-art microfabrication in depth due to its irreplaceable role in realizing next-generation magnetic neuromodulation. In addition to reviewing magnetic neuromodulation, this review will cover through-silicon vias (TSV), surface micromachining, photolithography, direct writing, and other fabrication technologies, supported by case studies, providing a framework for the integration of magnetic neuromodulation and microelectronics technologies.
CRIS-Team Scopus Importer:2024-11-01
Keywords: magnetic stimulation; microfabrication; nanoinvasive; neuromodulation; neurophysiology